REFLEXIONES SOBRE LA ENSEÑANZA DE LA FÍSICA - Burbano, Pedro Pablo; Investigador Fundación Patascoy. Asesor Sistema de Investigaciones ITP Sibundoy - Putumayo (2013)
This text approaches to pick up notions and to responds the questions: For what reason to teach Physics? Why to teach Physics? What to teach of Physics? How to teach Physics? It is important to make sorne analysis, reflection and to find arguments for improving the educational process in physics at leve! of primary, secondary and higher education.